THE INFLUENCE OF LOCAL FOOD BRAND IMAGE ON CONSUMER PURCHASE DECISION DURING COVID-19 PANDEMIC - Erny Hutabarat; Agus Pahala Tua (Journal of Management and Leadership, 2021)
The Covid-19 pandemic that occurred at the end of 2019 has caused an economic downturn in Indonesia and the government has also appealed to the public to immediately implement health protocols. As a result, many franchisees experienced a decline in revenue, including national and international franchises. The purpose of this study is to analyze the purchasing decisions of the community at the local franchise Martabak Roland in South Tambun, Bekasi, West Java. This local franchise brand image has a very good image, purchase intention is used in this study as an intervening variable. This research is a quantitative study using an online questionnaire as a data collection tool, with a sample of 100 respondents. Hypothesis testing uses the Structural Equation Model (SEM). The results showed that brand image and price had no significant effect on purchase intentions and food quality had no effect on purchase intentions. Meanwhile, the Purchase intention variable which is classified as moderate has a significant effect on the decision to purchase a local franchise during Covid-19